Geometric dimensioning and tolerancing application on pager - Teo, Edmund Hwee Yong. (2008)
The aim of the project is to perform reverse engineering on a pager, understand the functional relationships and communicate the geometric requirements and relationships on the drawings. A brief description on the manufacturing and assembly process of the pager and its parts are included to give the reader an insight on how engineering tolerances inter-relate and affect the final product. Application of GD&T are applied on several selected parts with descriptions on why those GD&T are particularly callout to control specific tolerances.